Kelas Daring Sinkronus dan Asinkronus di Sekolah Menengah Pariwisata di Indonesia: Aplikasi Teknologi dan Tantangan - Rido, Akhyar; Prakoso, Bagus Hary; Perez-Amurao, Analiza Liezl; Purba, Mariati; Siswanto, Heni Waluyo (Jurnal Sosioteknologi, 2024)
There has been an increasingly dominant use of technology in education institutions, yet limited studies holistically investigate the utilization of technological applications in tourism vocational high schools. This research explored the synchronous and asynchronous technological applications used and the challenges experienced by teachers and students of a tourism vocational high school in Indonesia, mainly in hotel and culinary online classrooms. This research employed a qualitative approach. Data were collected by observing four classes in two vocational schools in Yogyakarta and Bali. Interviews with five teachers and five students were also conducted on a voluntary basis. The findings indicate that teachers and students used various technological applications like Google Meet, Zoom, Microsoft Team, Cisco WebEx, Discord,and Skype for synchronous online learning. They also utilized more technological applications such as WhatsApp, YouTube, Google Classroom, Google Form, Telegram, Moodle, Screencast-O-Matic, Facebook, Instagram, Quizzes, Kahoot, and Twitterfor their asynchronous online learning. Both teachers and students faced technical, pedagogical, psychological, and personal challenges such as an unstable internet connection, a lack of technological literacy, incompatible gadgets, limited participation, work overload, demotivation, and a lack of focus on learning. To conclude, a number of technological applications were used to facilitate learning in hotel and culinary departments, even though there were many challenges that came with their usage. The results of this research can be used by relevant stakeholders preparing for future learning, especially in vocational high schools.